Objects in motion in the early modern world - Bleichmar, Daniela 1973-; Martin, Meredith (Meredith S.) (Chichester, West Sussex Malden, MA Wiley Blackwell, Association of Arts Historians, 2016)
"Objects in motion in the early modern world presents a collection of twelve original essays that examine the circulation of objects across a variety of global regions and cultures from the sixteenth to eighteenth centuries that reveal the importance of mobility for understanding the production, use, and meanings of early modern art. Individual essays trace the routes of an unusually wide range of cultural, geographical, and material examples -- including Persian silk textiles in Venice, Chinese porcelain along the Swahili Coast, exotic South Pacific bird specimens in Holland, and various European objects through India and Siam. The multiple mechanisms by which each of these objects were transported, translated, resisted, and consumed in the early modern period are carefully explored, as well as the various forms of mobility -- both physical and interpretive -- that each historical object experienced during this period. Collectively, essays reveal how mobility provides a vital means to reconsider traditional geographies and hierarchies associated with global exchange, particularly those that privilege Western Europe. Timely and provocative, objects in motion in the early modern world sheds important new light on the mobility of objects and cultural meaning in the early modern world -- and paves the way to a consideration of broader questions about art history and its disciplinary boundaries." -- Provided by publisher
Introduction: Objects in motion in the early modern world Meredith Martin and Daniela Bleichmar -- Exotica on the move: birds of paradise in early modern Holland Claudia Swan -- The Persian Madonna and child: Commodified gifts between diplomacy and armed struggle Sinem Arcak Casale -- Mirror reflections: Louis XIV, Phra Narai, and the material culture of kingship Meredith Martin -- An imperial Mughal tent and mobile sovereignty in eighteenth-century Jodhpur Zirwat Chowdhury -- History in pictures: translating the codex Mendoza Daniela Bleichmar -- Chinese porcelain and Muslim port cities: mercantile materiality in Coastal East Africa Sandy Prita Meier -- Chairs, writing tables, and chests: Indian Ocean furniture and the postures of commercial documentation in Coastal Yemen, 1700-40 Nancy Um -- Metamorphosis at the Mughal Court Jessica Keating -- Transporting India: The Gentil Album and Mughal manuscript culture Chanchal Dadlani -- Peepboxes, society, and visuality in early modern China Kristina Kleutghen -- From Byobu to Biombo: the transformation of the Japanese folding screen in colonial Mexico Sofia Sanabrais -- Nails, necklaces and curiosities: scenes of exchange in Bougainville's Tahiti Mar Sheriff
Includes index.
Keywords: Art and globalization; Art and society; Art, Modern -- Themes, motives